PERAN AFRICAN UNION (AU) DALAM MENGHADAPI PERSOALAN POLITISASI UPAH DI NIGERIA - Andansari, Nadya Tri; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The politicization of wages and social inequality in Nigeria has become a significant issue over the past decade. Although the African Union (AU) has issued various policies related to social justice and labour welfare, their impact on Nigeria's economic and social conditions remains a topic of debate. This study aims to analyze the role of the AU in responding to the politicization of wages and social inequality in Nigeria between 2012 and 2022. The findings reveal that while the AU has introduced policies to address social inequality and improve labour welfare, their implementation has been hindered by weak coordination with the Nigerian government, a lack of law enforcement, and domestic political interests. As a result, social protests persist, and social inequality continues to be a major issue in Nigeria. The study concludes that the AU needs to strengthen monitoring mechanisms and enforce stricter policies to more effectively address the politicization of wages. Keywords: African Union, Politicization of Wages, Social Inequality, Nigeria, Regional Organizations.